2022
DOI: 10.3389/fsurg.2022.930159
|View full text |Cite
|
Sign up to set email alerts
|

Superior calyceal access vs. other calyceal access in percutaneous nephrolithotomy: A systematic review and meta-analysis

Abstract: PurposeTo evaluate the superior calyceal access’s performance and safety in relation to other calyceal access during percutaneous nephrolithotomy (PCNL).MethodsThe suggested reporting items for systematic reviews and meta-analysis were used to conduct this meta-analysis (PRISMA). To find pertinent studies for this meta-analysis, we searched PubMed, Embase, Web of Science, and China National Knowledge Infrastructure (CNKI). Operation time and hospital stay are two secondary outcomes, whereas failed stone cleara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Ma et al. conducted a systematic review of 16 studies with 8541 patients to evaluate the effect and safety of placing tracts in the upper calyx during PCNL and concluded that upper calyceal access has better stone clearance and lower additional puncture rates without increasing complications 14 . However, evidence regarding the tract location during ECIRS is limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ma et al. conducted a systematic review of 16 studies with 8541 patients to evaluate the effect and safety of placing tracts in the upper calyx during PCNL and concluded that upper calyceal access has better stone clearance and lower additional puncture rates without increasing complications 14 . However, evidence regarding the tract location during ECIRS is limited.…”
Section: Discussionmentioning
confidence: 99%
“…10 Ma et al conducted a systematic review of 16 studies with 8541 patients to evaluate the effect and safety of placing tracts in the upper calyx during PCNL and concluded that upper calyceal access has better stone clearance and lower additional puncture rates without increasing complications. 14 However, evidence regarding the tract location during ECIRS is limited. Large stones in multiple calyces still pose a challenge in achieving stone-free status, 6 although the importance of tract location may be reduced with the use of f-URS compared with PCNL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation